Pitting Corrosion Model for Partial Prestressed Concrete (Pc) Structures in a Chloride Environment - Darmawan, M. S. (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2009)
Prestressed concrete structures cannot escape from corrosion problems, especially when they are subjected to very aggressive environment, such as chloride environment. For prestressed concrete structures, corrosion of prestressing strands may initiate structural collapse due to higher stress levels in the steel. Research on corrosion effect on concrete structures has mainly considered the effect of corrosion have on reinforced and full prestressed concrete structures. In this study, a structural framework will be developed to predict the flexural strength of partial prestressed concrete structures in a chloride environment. The framework developed will be combined with probability analysis to take into account the variability of parameters influencing the corrosion process.